The iliad of Homer and the odyssey - Homero (Great Books of the Western World, 1952)
The Iliad" is a full transcript of The Iliad hero myth by Samuel Butler in 1898. Butler translated the work into prose from the Homeric Greek for a broad audience. It contains all twenty-four books through 421 pages. Butler's version is readable for a layman audience. This work is attributed to a single man named Homer; however, many scholars do not accept this authorship claim. Text cover art Text: Full Translation, Collation (partial).